2013
DOI: 10.1002/jtr.1974
|View full text |Cite
|
Sign up to set email alerts
|

Celebrity Attachment and Behavioral Intentions: The Mediating Role of Place Attachment

Abstract: Film‐induced tourism has recently gained increased attention in academic research. Although previous literature has identified the existence of consumer–celebrity attachment, scant empirical studies have examined whether celebrity attachment influences behavioral intentions in a film tourism context. The purpose of this study is to examine the relationship between celebrity attachment and behavioral intentions as well as to clarify the role of place attachment. Survey data from 312 tourists in Taiwan indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 75 publications
(121 reference statements)
4
41
0
Order By: Relevance
“…Overall, TV news and documentaries appear to shape peoples' interest in certain destinations by providing them with myths, images and emotions, all of which being critical motivators for people to travel (Iwashita, 2008). This finding corroborates previous research on the positive effect visual media have on tourists' destination image and choice (Hudson et al, 2011;Gong & Tung, 2016;Pan, 2011;Shani, Chen, Wang & Hua, 2010;Wong & Lai, 2013).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Overall, TV news and documentaries appear to shape peoples' interest in certain destinations by providing them with myths, images and emotions, all of which being critical motivators for people to travel (Iwashita, 2008). This finding corroborates previous research on the positive effect visual media have on tourists' destination image and choice (Hudson et al, 2011;Gong & Tung, 2016;Pan, 2011;Shani, Chen, Wang & Hua, 2010;Wong & Lai, 2013).…”
Section: Resultssupporting
confidence: 84%
“…This type of information is perceived as unbiased by consumers, as they are considered more genuine, in contradistinction to induced image formation agents like traditional advertising (Gartner, 1993;Govers, Go & Kumar, 2007). Past research on visual media and destination image has mainly focused on how films, TV commercials and photos affect peoples' destination image (Gong & Tung, 2016;Pan, 2011;Pan, Lee & Tsai, 2014;Shani, Chen, Wang & Hua, 2010;Yen & Croy, 2016), destination choice (Hudson, Wang & Gil, 2011;Wong & Lai, 2013) and their on-site experience and behaviour (Kim, 2010;Siripis et al, 2013;Yen & Teng, 2015). Studies, in particular, have found that visual media increased peoples' awareness of places, had tourist inducing effects and influenced visitors' on-site experience (Kim & Assaker, 2014;Kim, 2012;Kim, Agrusa, Lee & Chon, 2007;Pan & Tsang, 2014;Riley, Baker & Van Doren, 1998; Siripis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the media effect studies, audience involvement and engagement with media content like stories and characters have been well addressed (Kim & Rubin, ; Rubin, Perse & Powell, ; Rubin & McHugh, ; Sood & Rogers, ; Kim, Long & Robinson, ). Some terms are used in the tourism literature to describe emotion and character involvements, such as empathic and vicarious involvement (Schofield, ; Lee et al ., ; Riley et al ., ; Kim & Richardson, ; Busby et al ., ; ) and celebrity involvement (Wong & Lai, ). Regardless, involvement is deemed the relative strength of the individual's cognitive structure to the focal object (O'Cass, ), and the term enduring involvement seems to cover the essential meanings of the involvement concept for this study as TV drama series is usually aired regularly over a longer period.…”
Section: Concepts and Hypothesesmentioning
confidence: 99%
“…A second group of articles constitutes a more homogenous subgroup distinguished by articles from authors such as Lopez et al (2015), Nicosia and Dallari (2015), Beaton and Cavicchi (2015), di Cesare and La Salandra (2015), Pennacchia (2015), Roberson and Grady (2015), Roberson and Grady (2015), Mercatanti (2015), D'Alessandro et al (2015), Puleo (2015) and Urso (2015), that focus their studies on the ways that film induces tourism. This group of articles also contains other articles that appear in the upper left corner of the figure as is the case, for example, of Wong and Lai (2015), and that differ in content from the remainder. This project also sought to grasp the focus of study, the theme studied, who conducted the studies and the main conclusions of the empirical studies examined (Table 1).…”
Section: Resultsmentioning
confidence: 99%